SERVICES E-FILING AND E-BILLING TO INCREASE TAX COMPLIANCE AND ACCEPTANCE - Agus Bandiyono; Mitsalina Choirun Husna (Dinasti International Journal of Education Management And Social Science, 2019)
The objective to be achieved by the author is to explain the process of e-filing and e-billing services at KPP Pratama Jakarta Palmerah and explain the level of compliance and the level of tax revenue in terms of improving public services, specifically from e-filing and e-billing services. The method used for this writing is a qualitative method with literature studies and field studies. In general, the mechanism e-filing makes it easier to monitor the services and with SPT data centralized at one source, it will simplify and speed up the SPT inspection process, because there is no need to collect SPT from dropbox locations for collection and checking. The level of tax compliance in the form of realization of SPT submission is not too affected by the mechanism e-filing